Publication Trends in English – Indonesian Translation and Vice Versa Between 2020-2024: A Systemic Literature Review of Scientific Journal - Sinaga, Inta Masni; Noryatin, Yeni (IKIP Siliwangi, 2026)
This study aims to investigate the publication trends in English-Indonesian translation and vice versa from 2020 to 2024, focusing on the distribution of research over time, the development of translation studies, and the theories used. This study, guided by theoretical perspectives from the Chesterman framework of translation studies, categorizes scholarly works into four key areas: Text Analysis and Translation, Multimedia Translation, Translation and Technology, and Translation Quality. Using a Systematic Literature Review, 55 articles published between 2020 and 2024 were analyzed to identify thematic patterns and yearly distribution. The results reveal a steady decline in publication numbers, from 16 articles in 2020 to 7 in 2024, indicating a potential decrease in research activity or a shift to alternative publication platforms. Translation studies analysis shows a strong dominance of Text Analysis and Translation (70.9%), while Multimedia Translation and Translation and Technology each account for 10.9%, and Translation Quality contributes 7.3%. These findings suggest a need for a broader exploration of emerging fields, such as audiovisual translation, machine translation, and translation pedagogy, as well as the incorporation of contemporary theoretical frameworks. The study recommends that researchers diversify their focus and that academic institutions revise curricula, encourage interdisciplinary collaboration, and strengthen research and publication support systems.